2012
DOI: 10.1590/s0004-28032012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss during cirrhosis is related to the etiology of liver disease

Abstract: -Context -Malnutrition is widely described in patients waiting for liver transplantation (LTx). However, risk factors associated with weight loss during liver disease have not yet been well studied. Objectives -The aim of this study was to assess weight loss and its risk factors during liver disease and up to the first appointment after transplantation. Patients who underwent LTx were retrospectively assessed for weight loss during liver disease while on the waiting list for LTx. The usual weight of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…They also found that weight changes were not associated with gender, diabetes mellitus, liver cirrhosis, and baseline body mass index or administration of ribavirin . Our patients showed higher incidence of weight gain 12 weeks post treatment that may be related to higher percentage of liver cirrhosis in their patients (59% vs 18.1% in our patients) with the associated potential malnutrition and metabolic abnormalities . Regarding the 12 weeks post treatment change of steatosis grade in patients with increased BMI; 16.1% showed decreased steatosis grade, 52.7% had no change in their steatosis grade while 31.2% had and increased steatosis grade.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…They also found that weight changes were not associated with gender, diabetes mellitus, liver cirrhosis, and baseline body mass index or administration of ribavirin . Our patients showed higher incidence of weight gain 12 weeks post treatment that may be related to higher percentage of liver cirrhosis in their patients (59% vs 18.1% in our patients) with the associated potential malnutrition and metabolic abnormalities . Regarding the 12 weeks post treatment change of steatosis grade in patients with increased BMI; 16.1% showed decreased steatosis grade, 52.7% had no change in their steatosis grade while 31.2% had and increased steatosis grade.…”
Section: Discussionsupporting
confidence: 44%
“…25 Our patients showed higher incidence of weight gain 12 weeks post treatment that may be related to higher percentage of liver cirrhosis in their patients (59% vs 18.1% in our patients) with the associated potential malnutrition and metabolic abnormalities. 26 Regarding Also, we reported significant lower steatosis in patients achieving 12 weeks SVR (SVR12) compared to non-responders. It has been suggested that hepatic steatosis may be, responsible for the DAAs.…”
Section: Discussionmentioning
confidence: 81%
“…Despite significant advances in the management of patients with cirrhosis, sarcopenia remains one of the most frequent clinical complications, reported in 30%‐70% of patients, that adversely affects outcomes including survival . Weight loss is a poor indicator of disease stage or severity especially because of the confounding effects of fluid retention, ascites and oedema . As such, muscle loss and alterations in adipose tissue mass in different compartments are difficult to identify on clinical evaluation alone.…”
Section: Introductionmentioning
confidence: 99%
“…20 Em relação ao tempo da perda de peso, quase metade dos pacientes (48%) tiveram perda de peso nos últimos 6 meses antes da internação, sendo que a maioria teve uma perda grave de peso. No estudo de Anastácio et al, 23 no qual foi avaliada a relação da perda de peso durante o curso da doença e a etiologia da cirrose, os achados foram que 68,7% (n ¼ 112) do total de pacientes (n ¼ 163) tinha perdido até 5% do seu peso corporal habitual e aproximadamente metade dos pacientes (48,5%; n ¼ 79) perdeu até 10%, ou seja, uma perda significativa de peso. Concluíram que a perda de peso foi um fator independente da idade, gênero, escolaridade e renda, porém esteve relacionada com a etiologia da doença hepática.…”
Section: Discussionunclassified